Peran Interaksi Sosial Dan Dukungan Emosional Dalam Meningkatkan Children Well-Being Anak - Aini Tsuroya Alghina; Taofik Rahman; Risbon Sianturi (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
Children’s well-being is a multidimensional concept encompassing emotional, social, and psychological aspects of child development. In the context of early childhood development, social interaction and emotional support are two fundamental factors that play a crucial role in shaping the quality of children’s well-being. This study aims to comprehensively analyze the role of social interaction and emotional support in improving children’s well-being through a literature review approach. The method used is a systematic literature review of various scientific sources, including reputable international and national journals as well as academic books published between 2022 and 2025. The findings indicate that positive social interactions with parents, teachers, and peers significantly contribute to the development of social skills, emotional regulation, and a sense of belonging in children. Furthermore, consistent and responsive emotional support has been proven to enhance children's sense of security, self-confidence, and psychological resilience. These two factors interact synergistically in creating a conducive developmental environment for children. The study also reveals that the quality of interaction is more influential than the quantity, highlighting the importance of emotional attachment in sustaining children's well-being. In conclusion, social interaction and emotional support play a highly strategic role in improving children’s well-being. Therefore, collaborative efforts among families, schools, and the broader social environment are essential to create a holistic and supportive ecosystem for child development